Effects of osmotic shock on production of β-carotene and glycerol in a naturally isolated strain of Dunaliella salina - Nima Montazeri-Najafabady, Manica Negahdaripour, Mohammad Hossein Salehi, Mohammad Hossein Morowvat, Saeedeh Shaker, Younes Ghasemi (Journal of Applied Pharmaceutical Science, 2016)
In the present study, the effects of hypo-osmotic and hyper-osmotic shock on β-carotene and glycerol production by a native strain of Dunaliella salina isolated from Maharlu Salt Lake, Fars province, Iran, were investigated. The amount of β-carotene and glycerol at 1 h, 2 h, 8 h and 24 h after initiating hypo-osmotic (1 M NaCl) and hyper-osmotic shocks (3 M NaCl); and at normal condition (2 M NaCl) were measured. At hyper-osmotic medium, β-carotene concentration reached to maximum amount after 2 h and remained constant up to 24 h. Even so, increasing of glycerol concentration was initiated after 2 h and reached the highest value at 24 h after salinity stress induction. At hypo-osmotic shock, β-carotene and glycerol concentrations were decreased. There are lots of lakes and salt marshes in Iran, which can be suitable environments for growing D. salina. So it seems that the isolated D. salina is potentially useful for planting in small locations to promote the commercial production of β-carotene and glycerol.
Keywords: &alpha; -Glucosidase inhibitor and antioxidant activity of procyanidin, an isolated compound from Quercus gilva Blume leaves